Skill of CMIP5 climate models in reproducing 20th century basic climate features in Central America. (2nd December 2014) - Hidalgo, Hugo G.; Alfaro, Eric J.
ABSTRACT A total of 107 climate runs from 48 Coupled Model Inter‐comparison Project 5 (CMIP5) general circulation models (GCMs) were evaluated for their ability to skillfully reproduce basic characteristics of late 20th century climate over Central America. The models were ranked according to metrics that take into consideration the mean and standard deviation of precipitation (pr) and surface temperature (tas), as well as the El Niño‐Southern Oscillation (ENSO)‐pr teleconnection. Verification was performed by comparing model runs to observations and a reanalysis dataset. Based on the rankings, the best 13 models were further evaluated. Not surprisingly, the models showed better skill at reproducing mean tas patterns throughout the year. The skill is generally low for mean pr patterns, except for some models during March, April, and May. With a few exceptions, the skill was low for reproducing the observed monthly standard deviation patterns for both pr and tas. The ENSO‐pr teleconnection was better simulated in the best 13 model runs compared to the sea‐surface temperature global pattern characteristic of ENSO which showed low skill. The Inter‐tropical Convergence Zone (ITCZ) appeared better modeled in July than in January. In January, there were instances of a double ITCZ pattern. Some models skillfully reproduced the seasonal distribution of the Caribbean Low‐Level Jet index (CLLJ). More detailed research evaluating the specific performance of the models on a variety of time‐scales and using parameters relevant to these and other climatic features of Central America is needed. This study facilitates a pre‐selection of models that may be useful for this task.